2016
DOI: 10.18632/oncotarget.9856
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17-5p regulated apoptosis-related protein expression and radiosensitivity in oral squamous cell carcinoma caused by betel nut chewing

Abstract: Betel nut chewing is associated with oral cavity cancer. Radiotherapy is one of the therapeutic approaches. Here, we used miR-17-5p antisense oligonucleotides (AS-ODNs) and human apoptosis protein array to clarify which apoptosis-related proteins are increased or decreased by miR-17-5p in betel nut chewing- oral squamous cell carcinoma OC3 cells. Furthermore, miR-17-5p AS-ODN was used to evaluate the radio-sensitization effects both in vitro and in vivo. An OC3 xenograft tumor model in severe combined immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…30 miR-17-5P has also been reported to promote proliferation and suppress apoptosis. [31][32][33] Other miRNAs, including miR-125b-5p, miR-21, and miR-146a, have been found to be enriched in MSC-Exos, regulating inflammation, promoting proliferation and showing curative effects. 34,35 F I G U R E 6 Exosomal miRNA-17-5P repressed ROS accumulation by regulating SIRT7 in a CTX-induced POI mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…30 miR-17-5P has also been reported to promote proliferation and suppress apoptosis. [31][32][33] Other miRNAs, including miR-125b-5p, miR-21, and miR-146a, have been found to be enriched in MSC-Exos, regulating inflammation, promoting proliferation and showing curative effects. 34,35 F I G U R E 6 Exosomal miRNA-17-5P repressed ROS accumulation by regulating SIRT7 in a CTX-induced POI mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-27a-3p can regulate transition from epithelial to mesenchymal in OSCC by targeting YAP1 [ 13 ]. The apoptosis-related protein expression and radiosensitivity in BQ-associated OSCC are regulated by microRNA-17-5p [ 14 ]. Metabolic shift in OSCC is mediated by microRNA-340 targeting glucose transporter-1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 41 By performing a similar study in radiotherapy, Wu et al identified that miRNA-17-5 p regulated radiosensitivity in oral squamous cell carcinoma. 42 The downregulated mir-17-5 p in esophageal adenocarcinoma cancer stem-like cells may promote the radioresistant phenotype. 43 …”
Section: Discussionmentioning
confidence: 99%